Parapapillary gamma zone associated with increased peripapillary scleral bowing: the Beijing Eye Study 2011 : clinical science - Xue, Can Can; Wang, Xiaofei; Han, Ying Xiang; Zhang, Qi; Zhang, Chun; Wang, Ya Xing; Jonas, Jost B. (British journal of ophthalmology, 2023)
Aims To investigate the association between the backward configuration of the peripapillary sclera (PPS), measured as PPS angle (PPSA), and presence and extent of parapapillary gamma zone. - Methods Out of the population-based Beijing Eye Study 2011, we randomly selected individuals free of optic nerve and retinal diseases. With Spectralis optical coherence tomography, we measured gamma zone (zone free of Bruch’s membrane (BM)) and determined the PPSA, defined as the angle between the anterior scleral surface lines from both sides of the optic nerve head (ONH). - Results The study included 678 individuals with age of 59.5±7.6 years (range: 50-90) and axial length of 23.5±1.3 mm (20.9-29.2). Gamma zone was more prevalent in eyes with larger PPSA (p=0.006) after adjustment for axial length (p<0.001) and BM opening area (p<0.001). Gamma zone width was positively associated with PPSA, axial length and BM opening area (all p<0.001) in multivariable analysis. Circular gamma zone was accompanied with larger PPSA as compared with focal gamma zone (19.9°±7.2° vs 6.3°±5.3°, p<0.001). Focal temporal gamma and focal inferior gamma had similar mean PPSA (p=0.69). However, the horizontal PPSA was significantly larger than the vertical PPSA in inferior gamma (6.9°±6.3° vs 4.7°±6.6°; p=0.005), while they were comparable in temporal gamma (6.1°±5.8° vs 6.3°±6.4°; p=0.073). - Conclusions A more backward bowing of the PPS was linearly and spatially associated with the presence, size and extent of gamma zone. It suggested that the BM and the sclera were closely related in participating the biomechanical behaviour of the ONH.